The Role Of Using Hris (Human Resource Information System) Technology In Human Resource Management At Pt Pegadaian Medan North Sumatera - Setiawan, Nashrudin; Wakhyuni, Emi; Azianda, M. Sultan (Universitas Dehasen Bengkulu, 2024)
This study aims to find how the influence of compensation, discipline, and HRIS Development on HR Management at PT Pegadaian Medan Branch, the research method used is quantitative with a Multiple Regression Analysis approach. The number of samples taken was 52 respondents calculated using the Slovin formula. The problem to be studied is to find the right model of application of Compensation, Discipline, and development of HRIS applications that will affect HR management in general and specifically increase the business productivity of Medan branch pawnshop employees to provide the best, both for internal companies and in the wider community to help the process of pawning goods or gold. The results of this study indicate that a) The results obtained from research conducted on HRIS variables (X1), namely there is an influence between HRIS on HR Management at PT Pegadaian Medan Petisah. This means that one of the factors of HR management is influenced by the use of HRIS by employees. Employees who can operate IT properly will get optimal performance results, b) The results obtained from the Work Discipline variable influence HR Management. Where the greater the discipline received by employees both internal and external, the greater the management of HR at PT. Pegadaian, c) The results obtained prove that compensation influences HR Management. This means that the amount of compensation obtained for their work provides enthusiasm that gives birth to maximum HR management.